PENGEMBANGAN KOMIK DIGITAL FISIKA BERBASIS WEBTOON DALAM MENINGKATKAN PEMAHAMAN SISWA PADA POKOK BAHASAN MATERI PEMANASAN GLOBAL - Wanda Aulia Agta, - (2023)
This research aims to develop a Webtoon-based digital physics comic on the subject matter of global warming with the comic name "FISIKUY: Belajar Fisika, Kuy!". The research was motivated by the results of observations of researchers while participating in the Educational Program Penguatan Profesional (P3K) at a high school in the city of Bandung regarding the lack of variety in the use of media in learning activities which is in line with the opinion of 76.67% of 30 students who feel bored when studying physics material using learning media, as well as the need for new technology-based innovations in learning activities in the era of globalization. Meanwhile, global warming is an environmental problem that is being discussed internationally and studied by students in schools, is one of the materials that is considered difficult because studying processes that occur in nature and cannot be observed directly the causes and impacts on these ecosystems. The research method used is Research and Development (R&D) with a 4-D development model consisting of the Define, Design, Develop, and Disseminate stages. To find out the feasibility level of the product, validation was carried out related to material, media, and language by 3 experts consisting of 2 lecturers and 1 high school level Indonesian teacher. Meanwhile, to find out the quality of its use in increasing students' understanding of global warming material, an understanding test was carried out using the One-group Pretest-Posttest Design on 30 students of class XI MIPA as early users of the product. The results showed that the product obtained a material feasibility value of 100% which qualified very feasible, media by 96% qualified very feasible, and language by 75% qualified feasible. The results of the improvement test from the pre-test and post-test results of students using the N-gain value method of 0.51 are included in the medium category, indicating that the use of Webtoon-based digital physics comics can improve students' understanding of the subject matter of global warming. Overall, students gave a positive response to the product being developed and commented that digital comics had an attractive appearance and made it easier for them to learn global warming material.